2022
DOI: 10.3390/d14070526
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phylogeography of Phoxinus, Delminichthys, Phoxinellus and Telestes in Dinaric Karst: Which Factors Have Influenced Their Current Distributions?

Abstract: The waters of the Dinaric Karst drain into both the Adriatic and the Black Sea basins. Precipitation is high, yet surface waters are scarce, with the exception of sinking streams. Dinaric Karst is a biodiversity hotspot, with diverse speleo- and epigean freshwater fauna. The distribution patterns of taxa in Dinaric Karst have arisen from a combination of vicariance and dispersal and their alteration over time. Within fishes, there are genera that include both species that are widespread and species with restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Moreover, hybrids between different genetic clades were detected at some sampling sites. However, additional studies showed that ranges of at least the species specifically studied were driven by natural processes rather than by recent human‐mediated translocations or introductions (Palandačić et al, 2020; Reier, Bogutskaya, & Palandačić, 2022; Reier, Kruckenhauser, et al, 2022). On the contrary, some clades are clearly geographically delimited, for example, Phoxinus krkae (Bogutskaya et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hybrids between different genetic clades were detected at some sampling sites. However, additional studies showed that ranges of at least the species specifically studied were driven by natural processes rather than by recent human‐mediated translocations or introductions (Palandačić et al, 2020; Reier, Bogutskaya, & Palandačić, 2022; Reier, Kruckenhauser, et al, 2022). On the contrary, some clades are clearly geographically delimited, for example, Phoxinus krkae (Bogutskaya et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among the highlighted problems to be addressed were the high intraspecific phenotypic diversity, which makes it difficult to diagnose morphologically similar species (Bogutskaya et al, 2019), and the insufficient information provided by the currently analysed molecular markers for final species delimitation (Palandači c et al, 2020). Finally, in contrast to most leuciscid fishes, it was found that the distribution of species (and/or mitochondrial [mt] clades) in European Phoxinus does not follow current zoogeographic patterns and drainage boundaries (Palandači c et al, 2015(Palandači c et al, , 2017a(Palandači c et al, , 2020Reier, Bogutskaya, & Palandači c, 2022;Reier, Kruckenhauser et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a side effect, the channel prevented the polje's natural flooding and enabled its agricultural exploitation [44]. Consequently, interventions have had a large impact on the surface and subterranean watercourses in the area [44,49,50], decimating the local fauna and pushing some of the narrowly endemic species to the very edge of existence [51][52][53].…”
Section: Geographic Settingmentioning
confidence: 99%
“…Authors also found several loci that can contribute to developing the population-specific, high-density SNP marker panels allowing the trade control of common carp production. Reier et al [10] explored mitochondrial genetic diversity of cyprinid fishes from the waters of the Dinaric Karst (Southern Europe), a biodiversity hotspot, that drain into the Adriatic and the Black Sea basins. The authors studied four leuciscid genera (Delminichthys, Phoxinus, Phoxinellus, and Telestes) that differed in size of the range and degree of specialization to dwelling in sinking streams in karst regions.…”
Section: Taxonomy Phylogeny and Evolutionmentioning
confidence: 99%